Star Trek’s Technological Predictions and Their Impact on Modern Innovation - Derah Sudjaniah; Bintoro Ariyanto; Indira Sascha; Arum Yulistiyaningsih; Mia Utami (Penerbit Goodwood, 2026)
Purpose: This study examines the relationship between futuristic technologies portrayed in the Star Trek series and the development of modern technological innovation, highlighting how science fiction can influence technological advancement. Research Methodology: A descriptive qualitative approach with a literature review method was employed. Data were collected from academic journals, books, technology reports, digital documentation, and technological representations presented in Star Trek. The data were analyzed using content, comparative, and interpretative analysis. Results: The findings reveal significant similarities between Star Trek technologies and contemporary innovations, including smartphones, digital tablets, artificial intelligence, smart assistants, AI-based translation systems, wearable devices, virtual reality, digital healthcare technologies, video communication, and smart automation. Conclusions: The study demonstrates that Star Trek serves not only as entertainment but also as a form of technological foresight that can inspire scientific research, innovation, and digital transformation. Limitations: This research is limited to secondary data and literature-based analysis without empirical evidence from technology developers, users, or audiences. Contributions: This study contributes to the fields of media studies, communication studies, digital transformation, and technology innovation by providing insights into the relationship between science fiction narratives and real technological advancement.